Place attachment through sensory-rich, emotion-generating place experiences in rural tourism. (September 2020) - Kastenholz, Elisabeth; Marques, Carlos Peixeira; Carneiro, Maria João
Abstract: Place attachment may be a relevant outcome of place experiences, connected to positive emotions felt at rural destinations. Especially for rural areas, where a loyal client base is often crucial for the survival of small businesses, such sustainability-enhancing place attachment is most valuable. Recently, researchers' attention has focused on the role of sensorial experiences in triggering such positive emotions associated with the travel experience leading to enhanced place attachment. However, the type of travel context, namely the condition of being a 'same-day visitor' or 'tourist', should also shape these relations. The present study analyses the impact of sensorial experiences (distinguishing sight, sound, smell and touch) on positive emotions (delight and relaxation, for high versus low arousal) and place attachment, additionally distinguishing tourists from excursionists. The study uses data collected through a one-year survey in three Portuguese hinterland villages (N = 453). As expected, tourists showed more intense sensorial experiences when compared to excursionists. These sensorial experiences triggered emotions and enhanced place attachment. Place attachment was triggered only by delight for excursionists and, in contrast, only by relaxation for tourists, with partly distinct senses leading to these emotional responses for both groups. Globally, the attachment mediation model of senses – emotions – attachment accounted for substantial variation of place attachment among excursionists, but had a weak predictive power for tourists, suggesting that their stronger affective bonds to the place depend on other factors, including other type of affective responses. Results are further detailed and discussed, both theoretically and in terms of possible implications for sustainability-yielding rural destination management and marketing. Highlights: Diverse sensory experiences have a positive influence on visitors' emotions in rural contexts, both on delight and relaxation. Length of stay moderates these relationships. Both delight and relaxation are triggered by a wider range of sensory stimuli among tourists than same-day visitors. Place attachment is a consequence of emotions, however with differences found between excursionists and tourists. The senses – emotions – attachment mediation model explains more variation of attachment among excursionists than tourists.